A drug database model as a central element for computer-supported dose adjustment within a CPOE system - Martin, Peter; Haefeli, Walter E.; Martin-Facklam, Meret (Journal of the American Medical Informatics Association, 2004)
The incidence of adverse drug reactions may be decreased by computerized physician order entry (CPOE) with decision support. The authors describe the development of a drug database model for computer-supported dose adjustment within a CPOE system. The following two core elements were included: (1) To allow electronic dose and volume calculation, the relation between strength (e.g., 5 mg/1 mL) and prescribed unit (e.g., 1 ampoule containing 2 mL) must be available in coded form. (2) The site of action along with the parent active ingredient, i.e., the pure drug without salt or ester, is necessary for linkage to knowledge bases. All complex examples of drugs that were examined could be described by the data model. With the ultimate goal of increasing prescribing effectiveness and quality the authors developed a drug database model for inclusion in a CPOE system, which allows dose calculations and may be coupled to decision support systems.
Gesehen am 19.05.2021